Profiling resilience: A latent profile analysis of German nurses' coping and resilience - Klingenberg, Ingo; Süß, Stefan (Frontiers in Health Services, 2022)
Introduction Because of the shortage of nurses, it becomes crucial for organizations and health systems to keep nurses in their workforce. As individual resilience is positively associated with organizational commitment and negatively with mental disorders, it may reduce nurses' intention to leave the profession. Thus, individual resilience gained attention in research. Nevertheless, there is no common conceptualization of individual resilience in the literature. Rather, three prevalent understandings exist. Due to these multiple understandings, the role of coping in the context of resilience remains unclear. Against this background, the aim of this study is to analyze the relationship between nurses' resilience and coping based on a person-centered approach. Methods This study presents a latent profile analysis based on a survey of 210 German nurses. The profiles were generated based on the Brief Resilience Scale and Brief COPE. The Perceived Workload of Nurses' Scale and sociodemographic data were considered as explanatory factors using nominal logistic regression. Further, the relation with possible consequences was tested by χ²-test using the Irritation Scale and KUT Commitment Measure. Results The study identifies four different profiles of coping and resilience. The profiles “resistant” and “social-active” show rather low irritations and high organizational commitment. The “passive” profile has lower irritation scores than the “solitary” profile does, but the “passive” profile is associated with more irritation than the “resistant” or the “social-active” profile. Whereas the other profiles include characteristics of resilience, the “solitary” profile has a vulnerable nature. The analysis shows that more coordination and information problems, higher age, and not being in a leadership role are associated with a higher probability of belonging to the “solitary” profile. The chance of belonging to the “solitary” profile is significantly higher for women than for men, whereas women have a significantly lower chance of belonging to the “resistant” profile, compared to men. Conclusion The analysis shows that the three prevalent understandings of resilience are appropriate but it also indicates that future scientific debate requires more precision in defining individual resilience. The study contributes to sharpening the definition of resilience as well as to understanding the link between coping and resilience.